Combretum aculeatum Vent (Combretaceae) hydroethanolic root bark extract attenuates D-galactoseinduced cognitive impairment, oxidative, and hippocampi dysfunction in mice - Galba Jean Beppe; Bertrand Mpoo Barga; Hervé Hervé Abaissou Ngatanko; Alice Irène Folefack; Nanou Gaël Allah-doum; Merline Nguedia; Alain Bertrand Dongmo; Théophile Dimo (Shahrekord University of Medical Sciences, 2024)
Introduction: Combretum aculeatum is a plant of Combretaceae family. In traditional medicine, it is used to treat schizophrenia. The aim of this study was to assess the possible impacts of hydroethanolic extract of C. aculeatum root bark on D-galactose (D-Gal)-induced amnesia in mice. Methods: Memory was tested using Y-maze test, radial arms maze (RAM), and new item appreciation. Mice brains were collected for histological and biochemical testing. Results: Combretum aculeatum substantially (P < 0.001) improved the ratio of spontaneous alternation versus negative control. In addition, discrimination index, and the time required to appreciate the new item were reversed considerably (P < 0.001) in mice receiving the extract opposed to the negative control fraction in the novel object appreciation test. The frequency of working memory mistakes was reversed in receiving extract categories versus negative control animals in RAM essay. Various doses of the extract substantially (P < 0.001) diminished the level of malondialdehyde (MDA), and crucially enlarged superoxide dismutase (SOD) and catalase activity as opposed to the negative control. Furthermore, all doses of the extract had a restructuring effect on the organization of hippocampal cells. Conclusion: Combretum aculeatum improved cognitive impairment possibly thought its antioxidant activity.